Вы находитесь на странице: 1из 3

# Math 1005 H Fall 2015

## Taylor Series and Fourier Series summary

Taylor and Maclaurin series

## Given a function f (x), the Taylor series of f (x) centred at a is

X
T (x) = cn (x − a)n
n=0

where
f (n) (a)
cn =
n!
(here f (n) (a) is the nth derivative of f evaluated at a). A Maclaurin series is just a
Taylor series with a = 0. The Taylor series for f (x) may or may not converge to f (x)
(we didn’t see enough in class to decide when f (x) = T (x)).

The radius of convergence of T (x) (or any other power series) is given by

cn
R = lim ,
n→∞ cn+1

provided the limit exists (if the limit doesn’t exist, the ratio test can be used to find
R). This means that T (x) converges absolutely as long as the distance between x and
a is less than R. That is, T (x) converges absolutely for |x − a| < R, or equivalently,
for a − R < x < a + R. T (x) may or may not converge at x = a ± R. In order to
find the interval of convergence, these endpoints must be tested, and either included
or excluded from the interval.

## Some important Taylor and Maclaurin series that we saw include:

x
X xn x2 x3
e = =1+x+ + + ... (radius of convergence is R = ∞)
n=0
n! 2! 3!

X (−1)n x2n+1 x 3 x5 x7
sin(x) = =x− + − + ... (radius of convergence is R = ∞)
n=0
(2n + 1)! 3! 5! 7!

X (−1)n x2n x2 x4 x6
cos(x) = =1− + − + ... (radius of convergence is R = ∞)
n=0
(2n)! 2! 4! 6!

X xn x2 x3
− ln(1 − x) = =x+ + + ... (radius of convergence is R = 1)
n=1
n 2 3

These can be used to find other Taylor and Maclaurin series. For example, to find
2
the Macluarin series of e−x , we can just replace each x with −x2 in the Maclaurin
series of ex , and simplify.
Fourier series for periodic functions

Given a periodic function f (x) with period T = 2L, the Fourier series of f (x) is

a0 X   nπx   nπx 
+ an cos + bn sin
2 n=1
L L

where
Z L Z L
1  nπx  1  nπx 
an = f (x) cos dx and bn = f (x) sin dx.
L −L L L −L L

The integration can actually be preformed over any interval of length 2L (for exam-
ple, from 0 to 2L). When computing the coefficients, find a0 separately from an when
n ≥ 1, as the integration in these two cases is generally done differently (bn only
appears for n ≥ 1, so there is no b0 ).

If both f and f 0 are piecewise continuous, the Fourier series of f (x) converges to the
average value of f , which is
1
(f (x−) + f (x+))
2
(here f (x−) is the left hand limit of f at x, and f (x+) is the right hand limit of f
at x). In particular, if f is continuous at x, the Fourier series of f at x converges to
f (x). If there is a jump discontinuity at x, the Fourier series of f at x converges to
the point half-way between the left and right limits of f at x.

If f is odd on [−L, L] or (−L, L), then an = 0 for all n. The Fourier sine series of
f (x) is

2 L
X  nπx  Z  nπx 
bn sin where bn = f (x) sin dx.
n=1
L L 0 L
If f is even on [−L, L] or (−L, L), then bn = 0 for all n. The Fourier cosine series of
f (x) is
∞ Z L
a0 X  nπx  2  nπx 
+ an cos where an = f (x) cos dx.
2 n=1
L L 0 L

## If we have a function f defined on an interval, we can find a Fourier series for f by

extending f to a periodic function. We have three ways to do this.

Let f (x) be defined on [a, b], and let T = b − a with L = T2 . The Fourier series of
f (x) on [a, b] is

a0 X   nπx   nπx 
+ an cos + bn sin
2 n=1
L L
where
Z b Z b
1  nπx  1  nπx 
an = f (x) cos dx and bn = f (x) sin dx.
L a L L a L

Essentially, we are letting f˜ be the T -periodic extension of f , and finding the Fourier
series for f˜. However, since f˜(x) = f (x) for x in [a, b], we can replace f˜ with f in the
formula for the coefficients.

Let f (x) be defined on [0, L]. The Fourier sine series of f (x) on [0, L] is
∞  nπx  Z L
X 2  nπx 
bn sin where bn = f (x) sin dx.
n=1
L L 0 L

Essentially, we are first extending f to an odd function f1 on [−L, L], then letting
f˜ be the 2L-periodic extension of f1 , and finding the Fourier series for f˜. Since the
function being integrated in the formula for the coefficients is even, the integral from
−L to L is equal to twice the integral from 0 to L. Since f˜(x) = f1 (x) = f (x) for x
in [0, L], we can replace f˜ with f in the formula for the coefficients.

Let f (x) be defined on [0, L]. The Fourier cosine series of f (x) on [0, L] is
∞ Z L
a0 X  nπx  2  nπx 
+ an cos where an = f (x) cos dx.
2 n=1
L L 0 L

Essentially, we are first extending f to an even function f1 on [−L, L], then letting
f˜ be the 2L-periodic extension of f1 , and finding the Fourier series for f˜. Since the
function being integrated in the formula for the coefficients is even, the integral from
−L to L is equal to twice the integral from 0 to L. Since f˜(x) = f1 (x) = f (x) for x
in [0, L], we can replace f˜ with f in the formula for the coefficients.